Noise behavior of vertical tunnel FETs under the influence of interface trap states. (August 2021) - Wangkheirakpam, Vandana Devi; Bhowmick, Brinda; Pukhrambam, Puspa Devi
Abstract: A detailed analysis of low frequency noise behavior of two different vertical TFETs namely n ​+ ​pocket VTFET and dual MOS capacitor (D-MOS) VTFET is presented in this work. Such analysis is performed to understand the limiting factors of their operations. The effect of the presence of both uniform and Gaussian type of interface trap charge distributions on the electrical performance of the devices under consideration are considered in the TCAD simulation study. The results report that the Flicker noise is dominant at low frequency whereas at high frequency, the diffusion noise is the superior noise component. The generation-recombination noise is found to be significant in the entire frequency range considered for the analysis. Lastly, comparison has been done on net drain current noise spectral density (Sid ) of some published work and this work.